2017
DOI: 10.1007/s10661-017-6056-6
|View full text |Cite
|
Sign up to set email alerts
|

Organic carbon causes interference with nitrate and nitrite measurements by UV/Vis spectrometers: the importance of local calibration

Abstract: Compared with sporadic conventional water sampling, continuous water-quality monitoring with optical sensors has improved our understanding of freshwater dynamics. The basic principle in photometric measurements is the incident light at a given wavelength that is either reflected, scattered, or transmitted in the body of water. Here, we discuss the transmittance measurements. The amount of transmittance is inversely proportional to the concentration of the substance measured. However, the transmittance is subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It should be kept in mind that water quality of a small stream can be very sensitive to rain and storm events compared with larger rivers [31,32]. Generally, in small streams, even short-term storm events can propagate an increase in discharge and a consequent increase in loading.…”
Section: Discussionmentioning
confidence: 99%
“…It should be kept in mind that water quality of a small stream can be very sensitive to rain and storm events compared with larger rivers [31,32]. Generally, in small streams, even short-term storm events can propagate an increase in discharge and a consequent increase in loading.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the online data of TSSs and COD, even after hourly averages, showed higher resolution and clear fluctuations of the wastewater quality within a week, which had much better representations of the wastewater quality trends. Studies have shown that site-specific calibration of online UV-Vis sensors enables accurate measurements of water quality by removing the interference of suspended particles on the UV absorbances [14,16,20,[32][33][34].…”
Section: Overview Of the Influent Water Quality Of The Wastewater Tre...mentioning
confidence: 99%
“…The greatest challenge in applying in situ UV–Vis technology for monitoring stream water quality is establishing robust relationships between specific water quality parameters and UV–Vis absorption spectra under the conditions with complicated biogeochemical constituents in the stream. Interference from compounds with distinctive absorbance can lead to overestimated water quality parameters (Uusheimo et al, 2017 ). Moreover, high concentrations of suspended particles, particularly during flood events, significantly alter the absorbance signals due to light scattering and shading.…”
Section: Introductionmentioning
confidence: 99%